Investigating the determinants of job satisfaction of Italian graduates: a model-based approach. Issue 1 (2nd January 2016) - Capecchi, Stefania; Piccolo, Domenico
Abstract : The paper explores the relationship between personal, economic and time-dependent covariates as determinants of the job satisfaction expressed by graduate workers. After discussing the main results of the literature, the work emphasizes a statistical modelling approach able to effectively estimate and visualize those determinants and their interactions with subjects' covariates. Interpretation and visualization of graduates' profiles are shown on the basis of a survey conducted in Italy; more specifically, the determinants of both satisfaction and uncertainty of the respondents are explicitly discussed.